Estimation of Resistor and Capacitor Parameters for Battery Aging in Energy Storage Systems - Saray, Merve; Boynuegri, Ali Rifat (IEEE, 2024)
This paper proposes a modified RC parameter estimation method for electrical analog battery models with limited bandwidth. The proposed method utilizes the electrical circuit components in the battery model behaviorally. Battery Thevenin Parameters Determination test is conducted under controlled conditions (constant room temperature, CC/CV (constant current/constant voltage) mode, 2C discharge rate to acquire data that can be used to predict the battery's true characteristics under aging. R and C parameters are critical factors influencing a battery's electrical behavior; they define its capacity, internal resistance, and voltage-current response. Due to battery aging, these R and C parameters also change. Consequently, estimating R and C parameters becomes essential for assessing the battery's aging state. This information can be leveraged to forecast battery lifespan and optimize battery replacement strategies. By applying a single pulse signal instead of multiple pulse signals applied in the HPPC (Hybrid Pulse Power Characterization) test, ECM circuit parameters can be determined by %99.77 in a shorter time. Furthermore, the estimated R and C parameters obtained using this method can be employed to determine the harmonic effects of Lithium-Ion Batteries (LIBs) within second-life applications (SLA).
Keywords: Battery; Second Life; Battery Thevenin Parameters Determination; ECM; Energy & Fuels; Engineering